Control and guidance: a comparative study of building and planning standards for age-friendly built environment in the UK and China - Xie, Fan; Li, Xiangfeng; Li, Xiaoming; Hou, Zhulin; Bai, Jing (Frontiers in Public Health, 2023)
The crux of building and planning standards for age-friendly built environment in all countries resides in the regulation of age-friendly built environment practices, yet there exist variations in the representation of content dimensions. The UK is distinguished by its discretionary approach to guidance, whereas China exhibits a highly controlled disposition. Control and guidance may appear to be antithetical, it is essential to recognize that the building and planning standards for age-friendly built environment in both countries never deviate from the legal constraints while providing guidance in achieving age-friendly environments, thus striking a delicate balance between control and guidance. The study examines the standard systems of national standards, local standards and organizational standards, as well as the three dimensions of foundation standards, generic standards and specialized standards. The analysis of building and planning standards for age-friendly built environment in the UK and China scrutinizes the disparities between control and guidance, identifying similarities and differences in the building and planning standard system and content dimensions of the two countries. This analysis serves as a valuable reference for the development of building and planning standards for age-friendly built environment in China.